Words, Bitter Meanings: A Pragmatic Study of Implicature in Melanie Martinez’s Gingerbread Man - Suci Pole Mappaita; Fadillah Pole Mappaita; Bayan Okenova (Researcher and Lecturer Society, 2025)
This study provides a pragmatic analysis of conversational implicature in Melanie Martinez’s song Gingerbread Man, focusing on how meaning is constructed beyond literal interpretation through linguistic choices. Each lyrical line was examined using Grice’s theory of implicature to determine how the four cooperative maxims, including Quantity, Quality, Relation, and Manner, are adhered to, violated, or intentionally flouted. The analysis reveals that flouting predominantly occurs in the maxims of Manner, Quality, and Quantity, indicating intentional ambiguity, exaggeration, and symbolic indirection throughout the lyrics. Such patterns demonstrate Martinez’s creative strategy of using metaphor, sensual imagery, and emotionally charged symbolism to communicate deeper messages surrounding desire, vulnerability, power imbalance, and nontraditional perceptions of romantic relationships. These findings highlight implicature as a poetic mechanism that enriches the narrative, enabling multilayered interpretation and emotional resonance beyond explicit meaning. The study further emphasizes the value of pragmatic theory in analyzing artistic texts, showing how linguistic inference uncovers nuanced meaning embedded in contemporary music. This research contributes to the growing intersection between linguistics and literary discourse and encourages future studies to explore implicature in Martinez’s broader body of work or compare multiple musical genres to better understand how artists employ pragmatic devices to express identity, social messages, and psychological complexity.